Controlled localizing multi-wall carbon nanotubes in polyvinylidene fluoride/acrylonitrile butadiene styrene blends to achieve balanced dielectric constant and dielectric loss. (18th August 2021) - Huang, Zhao-Xia; Zhao, Ming-Liang; Zhang, Gui-Zhen; Song, Jian; Qu, Jin-Ping
Abstract: Selectively localization of conductive fillers in polymer blends is able to tailor their dielectric properties. However, the controlled localization of these fillers is remaining a challenge. In this work, through a two-step melt compounding technique, we prepared polyvinylidene fluoride (PVDF)/acrylonitrile butadiene styrene (ABS)/multi-wall carbon nanotubes (MWCNTs) blends with controlled MWCNTs location. Structural characterizations were performed to reveal the relationship between processing parameters and the MWCNTs locations. Then, we showed the frequency-dependent dielectric constant (ε) and dielectric loss (tanδ) of each sample and obtained PVDF/ABS/MWCNTs ternary blend with balanced ε and tanδ of 165.1 and 0.20, respectively. Ultimately, the correlation between MWCNTs locations and the dielectric properties were established. For the first time, rather than the current understanding of achieving superior dielectric properties by locating the filler at interface, we put forward a brand new approach by controlling the fillers locating at both interface and the continuous phase, which could be a more effective route in enhancing the ε without improving the tanδ. We believe this work can pave us a new avenue towards fabricating polymer dielectrics with high ε and low tanδ through controlling localization of the conductive fillers been included. Graphical abstract: Image 1